Numerical Application of Effective Thickness Approach to Box Aluminium Sections - Elide Nastri (MDPI AG, 2021)
The ultimate behaviour of aluminium members subjected to uniform compression or bending is strongly influenced by local buckling effects which occur in the portions of the section during compression. In the current codes, the effective thickness method (ETM) is applied to evaluate the ultimate resistance of slender cross-sections affected by elastic local buckling. In this paper, a recent extension of ETM is presented to consider the local buckling effects in the elastic-plastic range and the interaction between the plate elements constituting the cross-section. The theoretical results obtained with this approach, applied to box-shaped aluminium members during compression or in bending, are compared with the experimental tests provided in the scientific literature. It is observed that the ETM is a valid and accurate tool for predicting the maximum resistance of box-shaped aluminium members during compression or in bending.